2015
DOI: 10.1021/acs.molpharmaceut.5b00119
|View full text |Cite
|
Sign up to set email alerts
|

Major Source of Error in QSPR Prediction of Intrinsic Thermodynamic Solubility of Drugs: Solid vs Nonsolid State Contributions?

Abstract: The main purpose of this study is to define the major limiting factor in the accuracy of the quantitative structure-property relationship (QSPR) models of the thermodynamic intrinsic aqueous solubility of the drug-like compounds. For doing this, the thermodynamic intrinsic aqueous solubility property was suggested to be indirectly "measured" from the contributions of solid state, ΔGfus, and nonsolid state, ΔGmix, properties, which are estimated by the corresponding QSPR models. The QSPR models of ΔGfus and ΔGm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 58 publications
2
36
0
Order By: Relevance
“…p K a values, Table ). In view of the high solubilities, and as it is difficult to develop predictive models for solubility, it was not studied further. We instead focused on the cell permeability of the four drugs.…”
Section: Resultsmentioning
confidence: 99%
“…p K a values, Table ). In view of the high solubilities, and as it is difficult to develop predictive models for solubility, it was not studied further. We instead focused on the cell permeability of the four drugs.…”
Section: Resultsmentioning
confidence: 99%
“…First, a combined experimental and theoretical study should be conducted in order to assess the influence of the molecular and crystal structures on pharmaceutically relevant properties. There are approaches linking the solubility of pharmaceutical crystals with its melting point (Perlovich, 2014;Abramov, 2015) and theoretical lattice energy evaluated by solid-state density functional theory (DFT) (Voronin et al, 2016). The literature survey of multicomponent crystals of dicarboxylic acids with various APIs conducted in our earlier work (Manin et al, 2015) has shown the influence of the melting point and carbon chain length of the salt/cocrystal former on the potential solubility of the API.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been suggested that up to 40% of new drug molecules are effectively insoluble 15 and up to 75% are classified as having low solubility by the Biopharmaceutics Classification System (BCS). 16,9 At the lead optimization stage, it is not practical to carry out experimental determinations of thermodynamic solubility on large libraries of compounds. As a result, computational methods are employed to make predictions of numerous properties including solubility.…”
Section: Introductionmentioning
confidence: 99%
“…9 The creation of standard experimental datasets for solubility prediction is on-going. 25 There are methods which apply physically motivated fitted equations 12 or full calculations from first principles 11,26 to solubility prediction.…”
Section: Introductionmentioning
confidence: 99%